(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This research investigates the impact of flipped learning on student achievement in English education. Flipped learning, which reverses the traditional classroom dynamic by shifting content delivery outside of class, has been increasingly used in educational settings. The purpose of this paper is to explore how flipped learning influences student engagement, motivation, and language proficiency in English education. The study reviews relevant literature and conduct a qualitative analysis of flipped learning’s effects on students in English language classrooms. The results suggest that flipped learning improves academic achievement by fostering active engagement,